Complications Associated with Fixed Prosthodontics in a Population Presenting for Treatment to a Dental School in Jeddah, Saudi Arabia - Aiman O. Johar, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Evaluating the types of fixed partial denture failure has a great importance in educating general dentists and laboratory technicians. The objective of this study is to determine complications associated with fixed partial denture and to examine the effect of service duration as well as the number of units on prevalence of these complications in the selected samples. Seventy five patients contributing a total of 309 units were included. Qualities of the present fixed partial dentures were clinically and radiographically assessed. Descriptive statistics and chi-square were used for data analyses. The results showed most common complication was shade mismatch 64%, over-contoured 59.9%, open margins 49.8% and caries 40.1%. The number of units and duration of service were found to influence most of the assessed complications. The prevalence of complications was high among the studied sample. An effective method to control dental disease and improve dental awareness in Saudi Arabia is recommended.